2007
DOI: 10.1016/j.sysconle.2006.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Lyapunov control of finite dimensional Schrödinger equations

Abstract: An implicit Lyapunov based approach is proposed for generating trajectories of a finite dimensional controlled quantum system. The main difficulty comes from the fact that we consider the degenerate case where the linearized control system around the target state is not controllable. The controlled Lyapunov function is defined by an implicit equation and its existence is shown by a fix point theorem. The convergence analysis is done using LaSalle invariance principle. Closed-loop simulations illustrate the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
111
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(112 citation statements)
references
References 23 publications
0
111
0
1
Order By: Relevance
“…1, we observe that the control field changes at dV /dt = 0, or Im(ab * ) = 0 in Eq. (12). Without loss of generality, a can be set to be a real number, and φ and γ 0 determine the design of the control field.…”
Section: A Evolution Operatormentioning
confidence: 99%
See 2 more Smart Citations
“…1, we observe that the control field changes at dV /dt = 0, or Im(ab * ) = 0 in Eq. (12). Without loss of generality, a can be set to be a real number, and φ and γ 0 determine the design of the control field.…”
Section: A Evolution Operatormentioning
confidence: 99%
“…It uses feedback design to construct control fields but applies the fields to a quantum system in an open-loop way. It provides us with a simple way to design control fields for the manipulation of quantum state transfer [7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A solution is to present the problem as a minimization of a cost functional, that describes the goal to be achieved, and eventually some other constraints. This approach leaded to procedures such as stochastic iterative approaches (e.g., genetic algorithms) [16], iterative critical point methods (monotonic algorithms) [17,24,28], trajectory tracking or local control procedures ( [2,5,9,12,18,20,22] etc.). One advantage of this class of methods is that we obtain explicit control fields.…”
Section: Introductionmentioning
confidence: 99%
“…Most papers have used the Hilbert-Schmidt (HS) distance as the most natural Lyapunov function and in this setting [4]- [6] showed that the target state is asymptotically stable under a sufficient condition equivalent to controllability of the linearized system for pure states represented by wavefunctions, although an additional control had to be added to fix the relative phase of the state. An alternative design based on an implicit Lyapunov function was proposed in [7] to render (pure) target states asymptotically stable when the linearized system is not controllable. The more general case of systems whose states must be represented by density operators was recently considered in [9], [10], but our analysis for generic quantum states [12], for instance, showed the dynamical landscape and convergence behavior to be more complicated than described in [10].…”
Section: Introductionmentioning
confidence: 99%